2000
DOI: 10.1103/physrevlett.84.3558
|View full text |Cite
|
Sign up to set email alerts
|

Threshold and Linewidth of a Mirrorless Parametric Oscillator

Abstract: We analyze the above-threshold behavior of a mirrorless parametric oscillator based on resonantly enhanced four wave mixing in a coherently driven dense atomic vapor. It is shown that, in the ideal limit, an arbitrary small flux of pump photons is sufficient to reach the oscillator threshold. We demonstrate that due to the large group velocity delays associated with coherent media, an extremely narrow oscillator linewidth is possible, making a narrow-band source of non-classical radiation feasible.Stable and l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 21 publications
(41 reference statements)
1
23
0
Order By: Relevance
“…Expanding these expressions into third order of the generated fields E 1 and E 2 reproduces the equations of [15]. Equations (23-26) together with the boundary-conditions…”
Section: Stationary Field Equations and Analytic Solutionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expanding these expressions into third order of the generated fields E 1 and E 2 reproduces the equations of [15]. Equations (23-26) together with the boundary-conditions…”
Section: Stationary Field Equations and Analytic Solutionsmentioning
confidence: 99%
“…Close to the threshold of oscillation an almost perfect suppression of quantum fluctuations of one quadrature amplitude of a combination mode of the generated fields occurs [13,14]. Also sufficiently above threshold light fields with beat-frequencies tightly locked to the atomic Raman-transition and extremely low relative bandwidth are generated [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A linear fluctuation analysis has shown that close to the threshold of oscillation an almost perfect suppression of quantum noise of one quadrature amplitude of a combination mode of the generated fields occurs [22,25]. In addition, sufficiently above threshold, light fields with beat-frequencies tightly locked to the atomic Raman-transition and extremely low relative bandwidth are generated [26].…”
Section: Introductionmentioning
confidence: 99%